1980
DOI: 10.1530/jrf.0.0600121
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizing capacity and morphology of fowl and turkey spermatozoa in hypotonic extender

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…Avian sperm appear prone to bending, especially in the region encompassing the base of the head, neck, midpiece and the adjacent segment of the principal piece [12]. A number of studies have reported on the fragility of the neck region of poultry sperm, which makes this region susceptible to damage [2,4,9,[12][13][14][15]32], particularly when the cells are exposed to adverse physiological influences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Avian sperm appear prone to bending, especially in the region encompassing the base of the head, neck, midpiece and the adjacent segment of the principal piece [12]. A number of studies have reported on the fragility of the neck region of poultry sperm, which makes this region susceptible to damage [2,4,9,[12][13][14][15]32], particularly when the cells are exposed to adverse physiological influences.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported on the fragility of the neck region of poultry sperm, which makes this region susceptible to damage [2,4,9,[12][13][14][15]32], particularly when the cells are exposed to adverse physiological influences. Various external factors such as osmolarity, storage time and temperature have been implicated in sperm bending [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the observation that cytoplasmic droplets (see below) are often associated with head bending also implicates inconsistency in the removal of residual cytoplasm during spermiation in the formation of bent heads. Distention of the plasmalemma induced by the use of hypotonic extender is also reported to cause head bending (towards the base of the nucleus) as well as various degrees of tail bending [37].…”
Section: Head Defectsmentioning
confidence: 99%